The association between dietary inflammatory index and non-alcoholic fatty liver disease: A systematic review and meta-analysis - Jingjing Lin; Mengna Huang; Lina Shen (PLoS ONE, 2026)
Background The Dietary Inflammatory Index (DII) is a literature-based tool designed to predict inflammation. Previous studies suggest a potential association between the DII and non-alcoholic fatty liver disease (NAFLD). However, the relationship between the DII and both the incidence and progression of NAFLD remains unclear. Methods Systematic literature searches were conducted in PubMed, Web of Science, Embase, Scopus, and the Cochrane Library up to July 2025. A random-effects model was applied, and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Sensitivity and subgroup analyses were performed to explore the sources of heterogeneity, while Egger’s test was used to assess publication bias. Review Manager 5.4 and STATA 15.0 were employed for statistical analysis. Results Eighteen studies involving 262,468 participants were included. The data indicated a significant association between the DII and NAFLD (OR = 1.33, 95% CI: 1.23–1.44; P < 0.00001) and between the DII and fibrosis (OR = 1.36, 95% CI: 1.20–1.54; P < 0.00001). Subgroup analysis identified geographic region and diagnostic criteria as sources of heterogeneity. Egger’s test revealed publication bias for NAFLD. Conclusion A high DII was associated with an increased risk of NAFLD and an increased risk of progression to fibrosis. Systematic review registration PROSPERO, identifier CRD42025632168.